Case Report: A Novel Mutation in NFKB1 Associated With Pyoderma Gangrenosum - Fang, Ran; Wang, Jun; Jiang, Xiao-yun; Wang, Shi-hao; Cheng, Hao; Zhou, Qing (Frontiers in Genetics, 2021)
Pyoderma gangrenosum (PG) is a rare, destructive inflammatory skin disease of which a painful nodule or pustule breaks down to form a progressively enlarging ulcer. Ulcerations associated with PG may occur after trauma or injury to the skin. The etiology has not been clearly elucidated. Our report described a PG patient with a heterozygous splice-donor-site mutation in NFKB1 (c.730+5G>A) causing the absence of exon8 and the formation of truncated p105 (p.Asp191_Lys244delinsGlu; p105delEx8), which lead to distinct symptoms of high fever and excessive inflammation in wound area after routine surgical procedures. The functional analysis showed the variant caused reduced phosphorylation of p105 and resulted in the decreased processing of p105 to p50. We conclude that the patient's symptoms were caused by dysregulation of the NF-κB signaling pathway.